FIRST YEAR STUDENT ATTITUDES TOWARD DISTANCE LEARNING - Banjević, Koviljka; Gardašević, Dragana; Nastasić, Aleksandra; Rošulj, Dragana (Journal of process management and new technologies, 2022)
Over the last two years, since the beginning of the COVID-19 pandemic, Higher Education Institutions (HEIs) in Serbia worked in the modality of distance learning – instructions and students` assignments were performed by distance, while colloquia and exams were realized in traditional conditions. Regardless of modality, HEIs have to ensure high-quality education in every single course. In this sense, the feedback from students is very important. The purpose of this study is to investigate students` attitudes about four dimensions of distance learning – fulfilment of preconditions, organization and realization of instructions, advantages/disadvantages of distance learning, communication and social interactions. Data was collected from 183 first-year students within three courses at The Academy of Applied Technical Studies Belgrade, and was processed in the SPSS software package. The research strategy included descriptive statistics, while the Likert scale was used to assess the satisfaction of the respondents. Analysis of variance and independent-sample t test were used to examine differences in opinions among different groups of respondents. The results of this study could be important for instructors, HEIs that operate in similar conditions, policymakers in the field of HE in Serbia, as well as for present and future research in this area.
Keywords: distance education; students` opinions; undergraduate students; the analysis of variance